Response to Ruth Armstrong. (August 2014) - Winter, Tim
The growth in Muslim chaplaincy provision in UK prisons disguises a paucity of resources, particularly in the area of offender rehabilitation. Islam's distinctive approach to antisocial behaviour, repentance and forgiveness needs to be better known among social administrators, particularly in the probation service.